2020
DOI: 10.18805/ijar.b-4131
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Plasma Osteopontin: A Marker for Potential Fertility in Dogs

Abstract: Background: Osteopontin (OPN) is an extracellular matrix protein with multifunctions and has been identified in the reproductive tract of both males and females. OPN from the seminal plasma (SP) has been closely associated with male fertility in several domestic animals. Different isoforms of OPN has been identified in the SP and sperm membrane in dogs but with unknown functions. The current study investigated the comparison of key canine sperm microscopic parameters and SP markers between dogs exhibiting diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In agreement with these established findings, our study further substantiates this relationship, revealing that higher OPN levels in the first fraction are associated with reduced sperm motility. This finding is in harmony with several studies in dogs, bulls, and boars, which have consistently shown a strong connection between sperm motility, fertility, and OPN levels [8,24,25]. These collective observations underscore the pivotal role of OPN in sperm functionality and its potential significance in reproductive studies.…”
Section: Exploring Opn's Role In Sperm Motility and Morphologysupporting
confidence: 89%
See 3 more Smart Citations
“…In agreement with these established findings, our study further substantiates this relationship, revealing that higher OPN levels in the first fraction are associated with reduced sperm motility. This finding is in harmony with several studies in dogs, bulls, and boars, which have consistently shown a strong connection between sperm motility, fertility, and OPN levels [8,24,25]. These collective observations underscore the pivotal role of OPN in sperm functionality and its potential significance in reproductive studies.…”
Section: Exploring Opn's Role In Sperm Motility and Morphologysupporting
confidence: 89%
“…Previous research by Lee et al [23] demonstrated a similar connection, highlighting OPN's protective role against apoptosis and oxidative damage in sperm cells. Abedin et al [8]) investigated deeper, elucidating specific pathways, such as MAP kinase and phosphoinositide 3-kinase, emphasizing OPN's influence on sperm motility. In agreement with these established findings, our study further substantiates this relationship, revealing that higher OPN levels in the first fraction are associated with reduced sperm motility.…”
Section: Exploring Opn's Role In Sperm Motility and Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…According to a previous study that the relationship between OPN expression and sperm integrin and CD44 receptor binding is demonstrated (Souza et al 2009;Gomes et al 2020) and it was shown to increase sperm motility, promoting acrosomal reactions, fertilization, and early embryonic development in cattle (Monaco et al 2009). Further, the activation mechanism of integrin and CD44 membrane receptors and signal transduction mechanisms, such as the activation of different pathways, especially Map kinase and phosphoinositide (PI) 3-kinase, which help sperm motile and produce energy (Abedin et al 2021). As a result, a higher OPN is associated with a larger percentage of motile sperm, as was seen in this study in extremely fertile Madura bulls.…”
Section: Discussionmentioning
confidence: 99%